Evolution of communication tools based on the virtual communication process - Erkin Kenenbaev; Izzetovna Gulnara; Tatyana Polatova; Asilbek Ergashev (The Bioscan, 2024)
The subject of the study is the patterns of combination of non-verbal and verbal means of communication, in the process of their appearance and interaction in written forms of Internet communication. The structural basis of the study is the study of the development of symbols of non-verbal components of communication (SNCC). The hypothesis of the study is that SNCC are becoming a new means of communication, combining the features of both written and oral speech.